Investigation of the relationship between air quality and health outcomes in Bilecik, Türkiye: A descriptive ecological study - Yücel, Mehtap; Küçükkendirci, Hasan (Scientific Reports in Medicine, 2026)
Objective: To evaluate temporal trends in air quality indicators and their ecological-level associations with respiratory and cardiovascular hospital admissions in two districts of Bilecik Province between 2020 and 2024.Methods: This ecological, retrospective study used annual district-level data from two public hospitals and two fixed air-monitoring stations in Bilecik city center and Bozüyük. Annual mean concentrations of PM₁₀, PM₂.₅, SO₂, NO₂, O₃ and CO were obtained from routine monitoring records. Hospital admissions were classified using ICD-10 codes for major respiratory and cardiovascular conditions. Descriptive trends were examined, and ecological co-variation between pollutants and total respiratory/cardiovascular admissions was assessed using Spearman’s rank correlation (p
Keywords: air pollution; PM₂.₅; respiratory diseases; cardiovascular admissions; ecological study